2018
DOI: 10.2147/ijn.s156616
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-targeting delivery of herb-based drugs with cell-penetrating/tumor-targeting peptide-modified nanocarriers

Abstract: Cancer has become one of the leading causes of mortality globally. The major challenges of conventional cancer therapy are the failure of most chemotherapeutic agents to accumulate selectively in tumor cells and their severe systemic side effects. In the past three decades, a number of drug delivery approaches have been discovered to overwhelm the obstacles. Among these, nanocarriers have gained much attention for their excellent and efficient drug delivery systems to improve specific tissue/organ/cell targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 155 publications
0
29
0
Order By: Relevance
“…However, they have limitations, some peptides lack stability as they are scavenged (especially, cationic peptides) by reticulo-endothelial system (RES) and also specificity deficient for cancerous cell targeting, leading to toxicity. To circumvent this issue, new generation multistage ligand-mediated nano-chemotherapeutics that are responsive to tumor microenvironment are designed, which are classified as follows: (a) activatable CPPs (ACPPs), (b) de-shielding systems, (c) “pop-up” systems, and (d) trojan-horse targeting systems (for detailed review, refer, Chen B. et al, 2017 ; Kebebe et al, 2018 ). In ACPPs, tumor microenvironment responsive materials are exploited to display CPPs either at lower pH or in presence of overexpression of ECM development-remodeling proteases, or in response to external stimuli of heat or light to a disease site (MacEwan and Chilkoti, 2013 ).…”
Section: Types Of Nanocarriersmentioning
confidence: 99%
“…However, they have limitations, some peptides lack stability as they are scavenged (especially, cationic peptides) by reticulo-endothelial system (RES) and also specificity deficient for cancerous cell targeting, leading to toxicity. To circumvent this issue, new generation multistage ligand-mediated nano-chemotherapeutics that are responsive to tumor microenvironment are designed, which are classified as follows: (a) activatable CPPs (ACPPs), (b) de-shielding systems, (c) “pop-up” systems, and (d) trojan-horse targeting systems (for detailed review, refer, Chen B. et al, 2017 ; Kebebe et al, 2018 ). In ACPPs, tumor microenvironment responsive materials are exploited to display CPPs either at lower pH or in presence of overexpression of ECM development-remodeling proteases, or in response to external stimuli of heat or light to a disease site (MacEwan and Chilkoti, 2013 ).…”
Section: Types Of Nanocarriersmentioning
confidence: 99%
“…16 It has been reported that encapsulation of anticancer drugs by nanoparticles could efficiently deliver drugs to tumor sites through an EPR effect and superior pharmacokinetics profiles in vivo, resulting in prolonged drug circulation and reduced systemic toxicity in vivo. 17 MPEG-PLA nanoparticles show high EE, stability and low clearance, which make it as a promising delivery tool for chemotherapeutic drugs. The amphiphilic property of MPEG-PLA enables the nanoparticles to selfassemble to be micelles and form a core-shell structure during the process of rehydration.…”
Section: Mpeg-pla Nanoparticles Encapsulated Cq-and Dox-induced Enhanmentioning
confidence: 99%
“…In our previous report, we reviewed the classification of polypeptide-and polypeptide-modified nanocarriers in detail. 258 In this report, recent research progress is summarized in the following paragraphs.…”
Section: Low-density Lipoprotein-modified Nanocarriersmentioning
confidence: 99%